2009
DOI: 10.1017/s1092852900025426
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime Subthreshold Mania is Related to Suicidality in Posttraumatic Stress Disorder

Abstract: Introduction: Although the association between mood disorders, and particularly bipolar disorders, comorbidity and suicidality in posttraumatic (PTSD) patients is well established, less information is available on the impact of subsyndromal mood symptoms. The aim of the present study was, thus, to explore the frequency and relationship between subthreshold mood symptoms, assessed by a specific and validated questionnaire, and suicidality in PTSD patients.Method: Sixty-five PTSD outpatients without bipolar diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 20 publications
2
27
0
Order By: Relevance
“…[36][37][38][39] A significant correlation between lifetime mood spectrum symptoms (assessed by the MOODS-SR, lifetime version) and increased suicidal ideation and/or attempts has previously been demonstrated in patients with complicated grief, 38 similar to that observed in patients with PTSD. [40][41][42] Interestingly, in a previous study, 38 we found significant correlations between complicated grief and subthreshold manic symptoms, ryhtmicity/vegetative function items, and depressive symptoms on the MOODS-SR. These relationships remained significant after controlling for comorbid Axis I disorders.…”
Section: Discussionmentioning
confidence: 53%
“…[36][37][38][39] A significant correlation between lifetime mood spectrum symptoms (assessed by the MOODS-SR, lifetime version) and increased suicidal ideation and/or attempts has previously been demonstrated in patients with complicated grief, 38 similar to that observed in patients with PTSD. [40][41][42] Interestingly, in a previous study, 38 we found significant correlations between complicated grief and subthreshold manic symptoms, ryhtmicity/vegetative function items, and depressive symptoms on the MOODS-SR. These relationships remained significant after controlling for comorbid Axis I disorders.…”
Section: Discussionmentioning
confidence: 53%
“…This may be considered in agreement with the available information reporting a link between subthreshold manic symptoms and suicidality in both the general population and in other psychiatric disorders. 23,25,[43][44][45][46][47] It is noteworthy that also the rhythmicity and vegetative function symptoms were related to increased suicidality. Although this matter is controversial, it can be concluded that some patients with different diagnoses may be more sensitive to weather-and/or season-related changes [48][49][50] and, as such, more prone to suicide.…”
Section: Discussionmentioning
confidence: 99%
“…22 Generally, the bipolar comorbidity, either the full-blown disorder or the subthreshold symptoms, is considered to enhance the vulnerability towards suicide in patients with different psychiatric disorders. [23][24][25][26] Since no information is available regarding CG, the aim of the present study was to explore the possible relationship between subthreshold mood spectrum symptoms and suicidality in patients with CG.…”
Section: Introductionmentioning
confidence: 99%
“…A consecutive sample of 65 out- and inpatients of both sexes (33 men and 32 women, mean age ± SD: 45 ± 14.8 years), with a DSM-IV-TR diagnosis of chronic PTSD, was recruited at the Section of Psychiatry of the Department of Clinical and Experimental Medicine, University of Pisa, Italy. Methods and sample characteristics were described in details in a previous study [ 38 ]. The majority of patients were married or living with a partner (N = 37, 56.9%), and had more than 8 years of education (N = 38, 58.4%).…”
Section: Methodsmentioning
confidence: 99%